Nurses assessment of symptoms in cancer patients - Tomić Sanja; Malenković Goran; Nikolić Ivana (Association of Nurses Technicians and Midwives, 2018)
Introduction: One of the leading health problems in the female population is cancer of gynecological organs. The illness and medical treatment modalities cause many physical and / or psychological symptoms that have a negative impact on recovery and are an obstacle to the continuation of the expected functioning in both the daily and professional environments. Aim: To determine the prevalence of the most common physical and psychological symptoms in the patient population with gynecological carcinoma after surgery in relation to the localization of malignant tumors. Material and methods: The research was conducted according to the type of cross section study by interviewing patients suffering from gynecological carcinoma at the Institute for Oncology of Vojvodina in Sremska Kamenica, at the Clinic for operative oncology, Department of Gynecology in the period from December 2017 to February 2018. A brief version of the Symptom Assessment Scale - Short Form [MSAS-SF.] Was used to assess the symptoms. Data processing included methods of descriptive and inferential statistics, for the data analysis, the statistical package SPSS 21 for Windows was used. Results: The average values of all supplements are the highest in the group of subjects with ovarian cancer. The highest mean value had a Global Distress Indicator. The total MSAS score indicates that psychological symptoms are dominant in relation to physical symptoms, for example, in divorced women with a secondary education level. The lack of energy and concern were the most common symptoms regardless of the localization of the carcinoma. Conclusion: The results of the study indicate that patients with gynecologic and gynecologic cancer patients show a higher proportion of psychological symptoms than physical ones. In the domain of psychological symptoms, concern had the highest incidence, while in the supplements of physical symptoms the lack of energy was highlighted. Physical and psychological symptoms are most common in divorced women with secondary education.